PEMBELAJARAN BERDIFERENSIASI DI RUANG KELAS (STUDI GURU PENGGERAK DI KECAMATAN SAMBAS) - Agustina, Agustina; Mashudi, Mashudi; Zakso, Amrazi; Aunurrahman, Aunurrahman; Hairida, Hairida (Universitas Tanjungpura, 2026)
This study aims to describe the implementation of differentiated learning in the classroom carried out by driving teachers in Sambas District. The implementation of differentiated learning studied from driving teachers includes the ability to compile teaching modules and carry out differentiated learning. This study uses a descriptive qualitative approach with the subject of the study being a driving teacher who teaches in four elementary schools in Sambas District. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Hubermen models. Triangulation is carried out by member check and technical triangulation. The results of the study showed that the driving teachers had prepared very well differentiated learning teaching modules, according to the learning plan components obtained a score of 97.57%. Carrying out the learning process was carried out very well, starting from the opening activities, core activities, and closing activities with a score of 94.92%. This study concludes that the pedagogic competence of driving teachers in Sambas District is very good in implementing differentiated learning according to the demands of the Merdeka curriculum.